Netnography Study: Suitability of Environmental Accounting Reporting of PT. Halmahera Persada Lygend on the Response of YouTube and Instagram Users - Jurana JURANA; Humaira MULIADY (International Journal of Environmental, Sustainability, and Social Science, 2024)
This study aims to understand the suitability between environmental accounting reporting of PT Halmahera Persada Lygend (HPAL) and the reality in the field based on community responses on the YouTube platform (https://youtube.com/@haritanickel?si=rimm0rUeZOuILjBq) and Instagram (https://www.instagram.com/harita.nickel?igsh=Z2J6MTVjMTBrd2cw). As part of Harita Nickel, HPAL is committed to operational sustainability by prioritizing environmental responsibility, which includes mangrove conservation, coral reef rehabilitation, environmentally friendly smelter development, and community empowerment of Obi Island. Using a netnography approach, this study analyzes user responses and comments on both platforms regarding HPAL's published sustainability reports and the implementation of environmentally friendly principles. The 2024 Merdeka Awards won by Harita Nickel also strengthened the positive perception of the company in terms of social and environmental responsibility. Based on data during the research period from September 14 to November 11, 2024, HPAL received 5,497 likes and 368 positive comments on YouTube, and 1,581 likes and 52 positive comments on Instagram, indicating that HPAL's environmental accounting implementation is in line with public perception and emphasizes the importance of synergy between industrial operations and social and environmental sustainability.